5x+2=-4(x-3)

Simple and best practice solution for 5x+2=-4(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+2=-4(x-3) equation:


Simplifying
5x + 2 = -4(x + -3)

Reorder the terms:
2 + 5x = -4(x + -3)

Reorder the terms:
2 + 5x = -4(-3 + x)
2 + 5x = (-3 * -4 + x * -4)
2 + 5x = (12 + -4x)

Solving
2 + 5x = 12 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
2 + 5x + 4x = 12 + -4x + 4x

Combine like terms: 5x + 4x = 9x
2 + 9x = 12 + -4x + 4x

Combine like terms: -4x + 4x = 0
2 + 9x = 12 + 0
2 + 9x = 12

Add '-2' to each side of the equation.
2 + -2 + 9x = 12 + -2

Combine like terms: 2 + -2 = 0
0 + 9x = 12 + -2
9x = 12 + -2

Combine like terms: 12 + -2 = 10
9x = 10

Divide each side by '9'.
x = 1.111111111

Simplifying
x = 1.111111111

See similar equations:

| 6b+8a=9 | | 180=(20y-10)+2x | | 25x+330=440 | | 7+2.5h=19-4x | | 14=4h-6 | | 3(d-1)=12 | | 230x+25=440 | | 195=56-v | | -16x--2=46 | | 5x+86=11x-10 | | r^2=9r-18 | | 10=2+2j | | -13+10x=-63 | | 7+2.5x=19-4x | | 25x+230.00=440.00 | | 31=3(w+7)-8w | | 4x+4=-6x+24 | | 6x+5+67=180 | | 7(3y+2)=-2 | | -12=-x+3x | | 8(5x+10)=40x-5 | | 24+8(c-3)=7c+5 | | 0.02x-0.2=4 | | 5(1+36)=-43+9b | | xy-3x-y=3 | | 5(x+6)=4(3-2x) | | f(x)=2x^2+11x | | 3=g | | 11x+6=11x-1 | | 5x+9=-17 | | x+2x-13=2 | | -7q+-14=-84 |

Equations solver categories